Evidence-Based Quality Improvement Training Programs: Building Staff Capability and Organizational Capacity. Issue 2 (April 2020) - Sarff, Laura; O'Brien, Roxanne
Abstract : Background: Patient harm from medical errors is frequently the result of poorly designed systems. Quality improvement (QI) training programs should build staff capability and organizational capacity for improving systems. Problem: Lack of internal expertise in QI and financial impact of hiring consultants deter organizations from developing QI training. Approach: One safety net hospital, with minimal resources, used evidence-based elements to create a Quality Academy Program. Outcomes: Significant outcomes demonstrated individual capability in undertaking QI initiatives. Staff who continued QI posttraining and the number of initiatives launched demonstrated organizational capacity. Feedback showed an increase in confidence with projects intended to improve care processes and patient outcomes. Conclusions: The elements shown to be essential in QI programs to build capability and capacity for organizational improvement can improve patient outcomes and organizational work processes as well as impact staff engagement and morale. Abstract : Supplemental Digital Content is Available in the Text.